Exploring the Elements of Multimedia Needed for Deaf and Hearing-impaired Students in Polytechnics - Abbas, L. N.; Md Khair, S. N.; Md Amin, N. D (Online Journal for TVET Practitioners, 2019)
Abstract: Educational revolution has been updated a long years ago and give more advantages in education world instead of making Malaysian as a developing country. The technology has been implemented in teaching and learning by fulfilling the recommendation government to apply the 21st century approaches. Multimedia-based learning is one of the best methods to deliver knowledge to deaf and hearing-impaired students. Hearing-impaired and deaf students really need this learning style to help them understand the input of studies. By implementing this 21st century approaches, we should not put aside teaching and learning of these students. Lack of hearing sense and lack of communication should not be a barrier for them to get the same education as normal person. This is because they have the right to have the same education as ours. However, the elements of multimedia need for hearing impaired and deaf students still questionable. This article exploring the elements of multimedia in teaching aid needed by deaf and hearing impaired students in polytechnics. Document analysis and informal interview have been used to explore the elements of multimedia. Four elements of multimedia elements have been revealed through this article which is sign language video, text, picture and audio. 3 lecturers have been interviewed to get the reason why all these elements of multimedia important in developing the teaching aids for deaf students in polytechnics. By integrate all those elements in teaching aids of deaf students hopefully will help them to have better understanding in learning.